The road ahead: emerging therapies for primary IgA nephropathy - Filippone, Edward J.; Gulati, Rakesh; Farber, John L. (Frontiers in Nephrology, 2025)
Primary IgA nephropathy (IgAN) is the most common form of primary glomerulopathy. A slowly progressive disease presenting in the young to middle-aged, most patients with reduced eGFR or proteinuria will progress to end-stage kidney disease (ESKD) in their lifetimes. The pathogenesis involves increased production of galactose-deficient IgA1 (Gd-IgA1) that forms immune complexes that deposit in the glomerulus, eliciting mesangial cell proliferation, inflammation, and complement activation. The backbone of therapy is supportive, including lifestyle modifications, strict blood pressure control, and renin-angiotensin system inhibition targeting proteinuria < 300 mg/day. Sodium-glucose transporter 2 inhibitors are indicated for persisting proteinuria or declining eGFR. Sparsentan is indicated for persisting proteinuria. Immunosuppression should be considered for all patients at risk for progression (persisting proteinuria and/or declining eGFR). To reduce Gd-IgA1 production, targeted-release budesonide is approved. Agents targeting B cell survival factors APRIL or BAFF/APRIL have significantly reduced Gd-IgA1 production and proteinuria in phase 2 trials but await phase 3 data for approval. To reduce inflammation, high-dose steroids are ineffective and toxic in Caucasian patients, although lower-dose regimens may be effective in Chinese patients. Complement inhibition is being actively studied. The factor B inhibitor iptacopan has conditional approval. The terminal pathway inhibitors cemdisiran and ravulizumab show promise in phase 2 studies. Our current approach for those requiring immunosuppression involves combining the reduction of Gd-IgA1 (nefecon) with suppressing the effects of inflammation (iptacopan). The optimal duration of such therapy is uncertain. Clearly, there is more to be learned with many trials underway.